Estimation of economic value and determinants of solid waste source-separation among urban-poor households in Lagos, Nigeria - Usman, Adam Shehu (2014)
The prior near-neglect of solid waste pollution in Lagos accorded its metropolis the status of the dirtiest city in the world. In a drastic policy response to address this environmental issue, Lagos state government privatized solid waste management service. The privatization model positions the government as an industrial regulator, via the Lagos Waste Management Authority (LAWMA). However, improved collection efficiency to avoid littering by the private companies, is noted to account for the fast-filling of existing dumpsites. To avoid associated risks, LAWMA proposes to introduce solid waste source-separation. Meanwhile, there is dearth of knowledge on the compensation amount households are willing to accept in respect to the cost of source-separating waste. This study sets five objectives to address this issue. Three of the objectives are original to this study. These include the use of design attribute relative importance index (DARII) to determine pre-design relative importance of choice experiment attributes. In addition, unlike existing studies, the dimensions of solid waste pollution concern are assessed to determine the form of concern households could activate in support of solid waste related pro-environmentalism. In the third original contribution, directional causality test was conducted to determine which of the potentially active dimensions of concern could be triggered to support solid waste source-separation. Besides all, this study is the first application of choice experiment to solid waste management in Nigeria. In achieving the study’s objectives, a few methods were combined for robustness purpose. These include the use of DARII, factor analyses, contingent valuation method, choice experiment and path analysis. This study focuses on the urban-poor market segment where non-compliance is reported the most in Lagos. Our results show that the most-preferred subset of service attributes for a source-separation program varies across market segments. In addition, we found three dimensions for solid waste pollution concern. Among these only two are found activated in support of source-separation. The directional causality test result shows that households are willing to practice solid waste source-separation on account of the consequence of pollution on themselves and other humans as against pollution consequence on the biosphere. Households’ minimum compensation amount was estimated at ₦ 45.50. Further investigation shows that the amount could be less than or greater than ₦ 45.50, depending on the source-separation program configuration implemented. The more the inclusion of service attribute levels desired by households in a configuration, the less is the required compensation for the corresponding welfare loss, and vice-versa. Based on findings, we suggest LAWMA to observe caution by considering market peculiarities in policy formulation on source-separation program. In addition, cost savings could be made over the planned regulatory 50% monthly waste bill discount proposed by the government to incentivize participation by households. In addition, LAWMA could induce biosheric values to reduce the perception of welfare loss from source-separation. The market scope examined in this study is narrow, thus, future research is suggested to focus on the market segments not captured in this study to allow a state-wide implementation of solid waste source-separation in Lagos.